Distribution of alleles, genotypes and haplotypes of the CYP2B6 (rs3745274; rs2279343) and CYP3A4 (rs2740574) genes in the Malian population: Implication for pharmacogenetics. Issue 29 (23rd July 2021) - Kassogue, Yaya; Diakite, Brehima; Kassogue, Oumar; Konate, Issa; Tamboura, Kadidiatou; Diarra, Zoumana; Maiga, Mamoudou; Dehbi, Hind; Nadifi, Sellama; Traore, Cheick Bougadari; Kamate, Bakarou; Dao, Sounkalo; et al.
Abstract : Abstract: Cytochrome P450 enzymes play a central role in the phase I biotransformation process of a wide range of compounds, including xenobiotics, drugs, hormones and vitamins. It is noteworthy that these enzymes are highly polymorphic and, depending on the genetic makeup, an individual may have impaired enzymatic activity. Therefore, the identification of genetic variants in these genes could facilitate the implementation of pharmacogenetic studies and genetic predisposition to multifactorial diseases. We have established the frequencies of CYP2B6 ( rs3745274; rs2279343) and CYP3A4 (rs2740574) alleles and genotypes in 209 healthy Malian subjects using TaqMan drug metabolism genotyping assays for allelic discrimination. Allele frequencies were 37% for CYP2B6 rs3745274 ; 38% for CYP2B6 rs2279343; and 75% for CYP3A4 rs2740574 respectively. Overall, the frequencies observed in Mali are statistically comparable to those reported across Africa except North Africa. The major haplotypes in CYP2B6 rs3745274 and CYP2B6 rs2279343 were represented by GA (60.24%) followed by TG (35.36%). We noted a strong linkage disequilibrium between CYP2B6 rs3745274 and CYP2B6 rs2279343 with D' = 0.91 and r 2  = 0.9. The frequencies of the genotypic combinations were 43.5% (GT/AG), 37.3% (GG/AA) and 11.5% (TT/GG) in the combination of CYP2B6-rs3745274 and CYP2B6- rs2279343; 26.8% (GT/CC), 25.4%, (GT/CT), 17.2% and GG/CT in the combination CYP2B6- rs3745274- CYP3A4 -rs2740574; 26.8% (AG/CC), 23.9% (AA/CC), 19.1% (AG/CT), and 11% (AA/CT) in the combination CYP2B6 -rs2279343- CYP3A4- rs2740574, respectively. The most common triple genotype was GT/AG/CC with 24.9%, followed by GG/AA/CC with 23.9%, GT/AG/CT with 16.7%, and GG/AA/CT with 10%. Our results provide new insights into the distribution of these pharmacogenetically relevant genes in the Malian population. Moreover, these data will be useful for studies of individual genetic variability to drugs and genetic predisposition to diseases.